Information design in the hypermedia - Passos, Ravi; Moura, Mônica (InfoDesign, 2007)
This work aims at discussing information design and its relation to hypermedia. Starting from the characterization of information design and similar terms, we confront herein information that elucidate activities related to that field, as well as its peculiarities and concepts involved in its utilization. This work also intends to point out hypermediatic characteristics that make information organization relevant, and to discuss the way in which such projective task is performed. As a result, we present and characterize the field which is responsible for treating information in interactive digital media.